Cut-Through Fractured Seepage Properties and Numerical Simulation of Sandstone after Different Temperature Treatments - Haopeng Jiang; Annan Jiang (Geofluids)
To explore the seepage characteristics of cut-through fractured rocks after different temperatures, sandstone in the Hunan area was selected as the research object. First, the influence degree of different temperatures on the permeability of fractured sandstone was studied, and the permeability variation of fractured sandstone with net confining pressure was revealed. The test data was nonlinearly fitted to prove that the relationship between permeability and net confining pressure conforms to the characteristics of the negative exponential function. Second, the macroscopic fractured state of sandstone after different temperature treatments was analyzed, and it is concluded that the inclination angle of the fracture surface decreases with the applied thermal temperature, the fracture surface gradually develops into a single shear failure surface, and the damage degree becomes more and more serious. Finally, the theoretical formula for the calculation of fractured seepage was introduced, and the FLAC3D embedded fish language was used to compile the seepage-stress coupling calculation program of the fractured sandstone after different temperature treatments. Numerical calculations were carried out based on samples with different fracture angles of fractured sandstone, and the calculated values were in good agreement with the test results. The research results can provide guiding significance for the research on the influence of high temperature in fire tunnel on the evolution of permeability of surrounding rock fissures.